Between fundamental rights and foundation: The position of human dignity in the Brazilian legal context - Demarchi, Clovis (Technium Social Sciences Journal, 2020)
The article focuses on Human Dignity and Fundamental Rights. The objective is to characterize Human Dignity as the foundation of Fundamental Rights. It is sought to demonstrate that the content of Human Dignity is the Fundamental Rights. The text is divided into five parts, initially with the proposal of creating a concept and the characterization for Human Dignity. In the next step, religious, political and philosophical elements of the idea of ??dignity are discussed. Then, the dignity in the Brazilian legal system is discussed, and the same occurs with Fundamental Rights. At the end of the article, there is a confrontation between Human Dignity and Fundamental Rights showing their intertwining. It was concluded that Human Dignity imposes limits on the actions of any organism and form of political or social organization. It is the foundation that determines the role of the Fundamental Rights. It is the condition of the existence of the human being. It is up to Human Dignity to bring the essence of what characterizes the human being in the juridical-social order. On the one hand, Fundamental Rights guarantee the realization of Human Dignity; on the other hand, dignity is concretized when Fundamental Rights are realized. The inductive method was used and the research was bibliographic and documentary. Predefined paragraph styles